1991
DOI: 10.1111/j.1365-2125.1991.tb05610.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infinitesimal drug dilutions on the pharmacokinetics of nalidixic acid and atenolol.

Abstract: 1. Ten healthy subjects received two treatments: a single 1 g oral dose of nalidixic acid (NA) followed 1 h later by either an infinitesimal dilution of the drug (NA 7CH) or by succussed water which served as placebo. The study was repeated 18 months later in 10 different subjects. 2. A further 10 healthy subjects received three treatments: a single 100 mg oral dose of atenolol (AT) followed 3 h later by either placebo or a dilution of AT (AT 7CH) or of bisoprolol (BI 7CH). The homoeopathic preparations were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study carried out on healthy volunteers found no significant difference in the nalidixic acid or atenolol levels in the blood among those people who took hetero-isotherapy of these substances in 7c, respectively 1 and 3 h after taking the original drug, compared to those who took a placebo. 16 As far as I have been able to ascertain, there appears to be no other published experiment using hetero-isotherapy in oncology.…”
Section: Do Hetero-isotherapies Risk Weakening the Action Of Chemothementioning
confidence: 99%
“…A study carried out on healthy volunteers found no significant difference in the nalidixic acid or atenolol levels in the blood among those people who took hetero-isotherapy of these substances in 7c, respectively 1 and 3 h after taking the original drug, compared to those who took a placebo. 16 As far as I have been able to ascertain, there appears to be no other published experiment using hetero-isotherapy in oncology.…”
Section: Do Hetero-isotherapies Risk Weakening the Action Of Chemothementioning
confidence: 99%